Glucose-driven uncoupling of methanogenesis from acidogenesis to generate carboxylates in anaerobic digestion: Insights into microbial dynamics and operational parameters - Hye Won Kim; Wangsuk Oh; Ping Liu; Xiao Su; Roderick I. Mackie (Biomass and Bioenergy, 2026)

Inhibition of biomethane production under antibiotics in poultry litter - Fayyaz Ali Shah; Qaisar Mahmood; Akhtar Iqbal; Roderick Ian Mackie (Arabian Journal of Geosciences, 2020)

Untangling the cecal microbiota of feral chickens by culturomic and metagenomic analyses - Chiara Ferrario; Giulia Alessandri; Leonardo Mancabelli; Eben Gering; Marta Mangifesta; Christian Milani; Gabriele Andrea Lugli; Alice Viappiani; Sabrina Duranti; Francesca Turroni; Maria Cristina Ossiprandi; Ricardo Hiyashi; et al. (Environmental Microbiology, 2017)
Summary Different factors may modulate the gut microbiota of animals. In any particular environment, diet, genetic factors and human influences can shape the bacterial communities residing in the gastrointestinal tract. Metagenomic approaches have significantly expanded our knowledge on microbiota dynamics inside hosts, yet cultivation and isolation of bacterial members of these complex ecosystems may still be necessary to fully understand interactions between bacterial communities and their host. A dual approach, involving culture‐independent and ‐dependent techniques, was used here to decipher the microbiota communities that inhabit the gastro intestinal tract of free‐range, broiler and feral chickens. In silico analysis revealed the presence of a core microbiota that is typical of those animals that live in different geographical areas and that have limited contact with humans. Anthropic influences guide the metabolic potential and the presence of antibiotic resistance genes of these different bacterial communities. Culturomics attempts, based on different cultivation conditions, were applied to reconstruct in vitro the microbiota of feral chickens. A unique strain collection representing members of the four major phyla of the poultry microbiota was assembled, including bacterial strains that are not typically retrieved from the chicken gut.

Outer membrane vesicles from Fibrobacter succinogenes S85 contain an array of carbohydrate‐active enzymes with versatile polysaccharide‐degrading capacity - Magnus Ø. Arntzen; Anikó Várnai; Roderick I. Mackie; Vincent G. H. Eijsink; Phillip B. Pope (Environmental Microbiology, 2017)
Summary Fibrobacter succinogenes is an anaerobic bacterium naturally colonising the rumen and cecum of herbivores where it utilizes an enigmatic mechanism to deconstruct cellulose into cellobiose and glucose, which serve as carbon sources for growth. Here, we illustrate that outer membrane vesicles (OMVs) released by F. succinogenes are enriched with carbohydrate‐active enzymes and that intact OMVs were able to depolymerize a broad range of linear and branched hemicelluloses and pectin, despite the inability of F. succinogenes to utilize non‐cellulosic (pentose) sugars for growth. We hypothesize that the degradative versatility of F. succinogenes OMVs is used to prime hydrolysis by destabilising the tight networks of polysaccharides intertwining cellulose in the plant cell wall, thus increasing accessibility of the target substrate for the host cell. This is supported by observations that OMV‐pretreatment of the natural complex substrate switchgrass increased the catalytic efficiency of a commercial cellulose‐degrading enzyme cocktail by 2.4‐fold. We also show that the OMVs contain a putative multiprotein complex, including the fibro‐slime protein previously found to be important in binding to crystalline cellulose. We hypothesize that this complex has a function in plant cell wall degradation, either by catalysing polysaccharide degradation itself, or by targeting the vesicles to plant biomass.

Age, introduction of solid feed and weaning are more important determinants of gut bacterial succession in piglets than breed and nursing mother as revealed by a reciprocal cross‐fostering model - Gaorui Bian; Shouqing Ma; Zhigang Zhu; Yong Su; Erwin G. Zoetendal; Roderick Mackie; Junhua Liu; Chunlong Mu; Ruihua Huang; Hauke Smidt; Weiyun Zhu (Environmental Microbiology, 2016)
Summary A reciprocal cross‐fostering model with an obese typical Chinese piglet breed and a lean Western breed was used to identify genetic and maternal effects on the acquisition and development gut bacteria from birth until after weaning. Pyrosequencing of 16S rRNA genes results revealed an age‐ and diet‐dependent bacterial succession process in piglets. During the first 3 days after birth, the bacterial community was relatively simple and dominated by Firmicutes with 79% and 65% relative abundance for Meishan and Yorkshire piglets, respectively. During the suckling period until day 14, the piglet breed and the nursing mother lead to increasing differentiation of the fecal bacterial community, with specific bacteria taxa associated with breed, and others with the nursing sow most likely due to its milk composition. Although the effect of nursing mother and the breed were evident through the suckling period, the introduction of solid feed and subsequent weaning were the major events occurring that dominated succession of the gut microbiota in the early life of piglets. This piglet cross‐fostering model is a useful tool for studying the effects of diet, host genetics and the environment on the development and acquisition of the gut microbiota and over longer studies the subsequent impact on growth, health and performance of pigs.

Cellulose degradation in the human gut: Ruminococcus champanellensis expands the cellulosome paradigm - Isaac Cann; Rafael C. Bernardi; Roderick I. Mackie (Environmental Microbiology, 2016)

Herbivorous rodents ( N eotoma spp. ) harbour abundant and active foregut microbiota - Kevin D. Kohl; Aaron W. Miller; James E. Marvin; Roderick Mackie; M. Denise Dearing (Environmental Microbiology, 2014)
Summary Symbiotic gut microbes have facilitated the success of herbivorous mammals, which are generally grouped into foregut‐ and hindgut‐fermenters. However, rodents are primarily herbivorous and exhibit a variety of gastrointestinal anatomies. Most rodents house microbes in hindgut chambers, such as the caecum and colon. Some rodents also exhibit stomach segmentation with a foregut chamber proximal to the stomach. For over a century, scientists have hypothesized that this foregut chamber houses a microbial community, yet this has never been explicitly examined. We investigated the capacity of each of the gut regions to house microbes by measuring size, pH , bacterial cell density, concentrations of microbial metabolites and digesta transit time in woodrats ( N eotoma spp. ). We also compared microbial communities across gut chambers, as well as faeces, using 16 S rRNA sequencing. This allowed us to test the appropriateness of using faeces as a proxy for microbial communities of other gut chambers. We found that woodrats house foregut microbial communities with similar density and volatile fatty acid concentrations to rumen ecosystems. Resident microbial communities varied between gut chambers, and faecal bacterial communities were significantly different from caecal and colonic communities. The foregut microbiota may provide a number of physiological services to the host.

Dietary Supplementation of Usnic Acid, an Antimicrobial Compound in Lichens, Does Not Affect Rumen Bacterial Diversity or Density in Reindeer - Trine Glad; Perry Barboza; Roderick I. Mackie; André-Denis G. Wright; Lorenzo Brusetti; Svein D. Mathiesen; Monica A. Sundset (Current Microbiology, 2014)

H alomonas sulfidaeris ‐dominated microbial community inhabits a 1.8 km‐deep subsurface C ambrian S andstone reservoir - Yiran Dong; Charu Gupta Kumar; Nicholas Chia; Pan‐Jun Kim; Philip A. Miller; Nathan D. Price; Isaac K. O. Cann; Theodore M. Flynn; Robert A. Sanford; Ivan G. Krapac; Randall A. Locke; Pei‐Ying Hong; et al. (Environmental Microbiology, 2014)
Summary A low‐diversity microbial community, dominated by the γ ‐proteobacterium H alomonas sulfidaeris , was detected in samples of warm saline formation porewater collected from the C ambrian Mt. S imon S andstone in the I llinois B asin of the N orth A merican M idcontinent (1.8 km/5872 ft burial depth, 50° C , pH 8, 181 bars pressure). These highly porous and permeable quartz arenite sandstones are directly analogous to reservoirs around the world targeted for large‐scale hydrocarbon extraction, as well as subsurface gas and carbon storage. A new downhole low‐contamination subsurface sampling probe was used to collect in situ formation water samples for microbial environmental metagenomic analyses. Multiple lines of evidence suggest that this H . sulfidaeris ‐dominated subsurface microbial community is indigenous and not derived from drilling mud microbial contamination. Data to support this includes V 1‐ V 3 pyrosequencing of formation water and drilling mud, as well as comparison with previously published microbial analyses of drilling muds in other sites. Metabolic pathway reconstruction, constrained by the geology, geochemistry and present‐day environmental conditions of the Mt . S imon S andstone, implies that H . sulfidaeris ‐dominated subsurface microbial community may utilize iron and nitrogen metabolisms and extensively recycle indigenous nutrients and substrates. The presence of aromatic compound metabolic pathways suggests this microbial community can readily adapt to and survive subsurface hydrocarbon migration.

Impact of different bioenergy crops on N‐cycling bacterial and archaeal communities in soil - Yuejian Mao; Anthony C. Yannarell; Sarah C. Davis; Roderick I. Mackie (Environmental Microbiology, 2013)
Summary Biomass production for bioenergy may change soil microbes and influence ecosystem properties. To explore the impact of different bioenergy cropping systems on soil microorganisms, the compositions and quantities of soil microbial communities (16S rRNA gene) and N‐cycling functional groups ( nifH , bacterial amoA , archaeal amoA and nosZ genes) were assessed under maize, switchgrass and Miscanthus x giganteus at seven sites representing a climate gradient (precipitation and temperature) in Illinois, USA. Overall, the site‐to‐site variation in community composition surpassed the variation due to plant type, and microbial communities under each crop did not converge on a ‘typical’ species assemblage. Fewer than 5% of archaeal amoA , bacterial amoA , nifH and nosZ OTUs were significantly different among these crops, but the largest differences observed at each site were found between maize and the two perennial grasses. Quantitative PCR revealed that the abundance of the nifH gene was significantly higher in the perennial grasses than in maize, and we also found significantly higher total N in the perennial grass soils than in maize. Thus, we conclude that cultivation of these perennial grasses, instead of maize, as bioenergy feedstocks can improve soil ecosystem nitrogen sustainability by increasing the population size of N‐fixing bacteria.

Monitoring airborne biotic contaminants in the indoor environment of pig and poultry confinement buildings - Pei‐Ying Hong; Xiangzhen Li; Xufei Yang; Takumi Shinkai; Yuanhui Zhang; Xinlei Wang; Roderick I. Mackie (Environmental Microbiology, 2012)
Summary Given the growing concerns over human and animal health issues related to confined animal feeding operations, an in‐depth examination is required to monitor for airborne bacteria and associated antibiotic resistance genes. Our 16S rRNA‐based pyrosequencing revealed that the airborne microbial community skewed towards a higher abundance of Firmicutes (> 59.2%) and Bacteroidetes (4.2–31.4%) within the confinement buildings, while the office environment was predominated by Proteobacteria (55.2%). Furthermore, bioaerosols in the confinement buildings were sporadically associated with genera of potential pathogens, and these genera were more frequently observed in the bioaerosols of pig and layer hen confinement than the turkey confinement buildings and office environment. High abundances of tetracycline resistance genes (9.55 × 10 2 to 1.69 × 10 6 copies ng −1 DNA) were also detected in the bioaerosols sampled from confinement buildings. Bacterial lineages present in the poultry bioaerosols clustered apart from those present in the pig bioaerosols and among the different phases of pig production, suggesting that different livestock as well as production phase were associated with a distinct airborne microbial community. By understanding the diversity of biotic contaminants associated with the different confinement buildings, this study facilitates the implementation of better management strategies to minimize potential health impacts on both livestock and humans working in this environment.

Ecological drift and local exposures drive enteric bacterial community differences within species of Galápagos iguanas - EMILY W. LANKAU; PEI‐YING HONG; RODERICK I. MACKIE (Molecular Ecology, 2012)
Diet strongly influences the intestinal microbial communities through species sorting. Alternatively, these communicates may differ because of chance variation in local microbial exposures or species losses among allopatric host populations (i.e. ecological drift). We investigated how these forces shape enteric communities of Galápagos marine and land iguanas. Geographically proximate populations shared more similar communities within a host ecotype, suggesting a role for ecological drift during host colonization of the islands. Additionally, evidence of taxa sharing between proximate heterospecific host populations suggests that contemporary local exposures also influence the gut community assembly. While selective forces such as host‐bacterial interactions or dietary differences are dominant drivers of intestinal community differences among hosts, historical and contemporary processes of ecological drift may lead to differences in bacterial composition within a host species. Whether such differences in community structure translate into geographic variation in benefits derived from these intimate microbial communities remains to be explored.

Characterization of the gene encoding glutamate dehydrogenase (gdhA) from the ruminal bacterium Ruminococcus flavefaciens FD-1 - Dionysios A. Antonopoulos; Rustam I. Aminov; Paul A. Duncan; Bryan A. White; Roderick I. Mackie (Archives of Microbiology, 2003)

Desulfotomaculum genus‐ and subgenus‐specific 16S rRNA hybridization probes for environmental studies - Krassimira R. Hristova; Margit Mau; Dandan Zheng; Rustam I. Aminov; Roderick I. Mackie; H. Rex Gaskins; Lutgarde Raskin (Environmental Microbiology, 2000)
Based on comparative analysis of 16S rRNA sequences and the recently established phylogeny of the genus Desulfotomaculum , a set of phylogenetically nested hybridization probes was developed and characterized. A genus‐specific probe targets all known Desulfotomaculum species (with the exception of Desulfotomaculum acetoxidans ), and five specific probes target subclusters within the Desulfotomaculum genus. The dissociation temperature of each probe was determined experimentally. Probe specificities were verified through hybridizations with pure culture rRNA isolated from a wide variety of target and non‐target organisms and through an evaluation of probe ‘nesting’ using samples obtained from four different environments. Fixation and hybridization conditions for fluorescence in situ hybridizations were also optimized. The probes were used in quantitative membrane hybridizations to determine the abundance of Desulfotomaculum species in thermophilic anaerobic digesters, in soil, in human faeces and in pig colon samples. Desulfotomaculum rRNA accounted for 0.3–2.1% of the total rRNA in the digesters, 2.6–6.6% in soil, 1.5–3.3% in human faeces and 2.5–6.2% in pig colon samples.

Amino acid utilization by the ruminal bacterium Synergistes jonesii strain 78-1 - Christopher S. McSweeny; Milton J. Allison; Roderick I. Mackie (Archives of Microbiology, 1993)